2021
DOI: 10.3892/ol.2021.12469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidants coenzyme Q10 and β‑carotene on the cytotoxicity of vemurafenib against human malignant melanoma

Abstract: Melanoma is a type of highly invasive skin cancer derived from melanocytes with poor prognosis. Vemurafenib (PLX4032) is a clinically approved targeted therapeutic for BRAF mutant melanoma that has a high therapeutic response rate and significantly prolongs the overall survival time of patients with melanoma. Antioxidants have been widely used as supplements for cancer prevention and for decreasing the side effects of cancer therapy. However, antioxidants can also protect cancer cells from oxidative stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…This implies that STIG may be a promising agent to treat melanoma (Figure 8). Previous studies have suggested the use of antioxidants for melanoma prevention or treatment [43,50]. The skin is continuously exposed to exogenous oxidative stress, with melanocytes particularly vulnerable due to the melanogenesis process, which generates ROS [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that STIG may be a promising agent to treat melanoma (Figure 8). Previous studies have suggested the use of antioxidants for melanoma prevention or treatment [43,50]. The skin is continuously exposed to exogenous oxidative stress, with melanocytes particularly vulnerable due to the melanogenesis process, which generates ROS [51].…”
Section: Discussionmentioning
confidence: 99%
“…Lowering local ROS levels enhances the immune response to melanoma by inhibiting PD-L1 signaling in vivo [53,57]. Quercetin is excellent Previous studies have suggested the use of antioxidants for melanoma prevention or treatment [43,50]. The skin is continuously exposed to exogenous oxidative stress, with melanocytes particularly vulnerable due to the melanogenesis process, which generates ROS [51].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the administration of CoQ10 in a breast cancer cell line reduced the activity of matrix metalloproteinase II, a key promotor of cancer cell invasion and metastasis [85]. In cultured melanoma cells, CoQ10 demonstrated an inhibitory effect on cell proliferation and migration/invasion when used individually or in combination with vemurafenib, despite an apparent protective effect of CoQ10 in protecting melanoma cells from apoptosis induction [86]. In a rat temozolomide-resistant glioma cell line, the co-administration of CoQ10 increased the efficacy of temozolomide in reducing cell proliferation and invasiveness [87].…”
Section: Cell Culture Studiesmentioning
confidence: 99%
“…On the contrary, β-carotene did not exhibit anti-proliferative effects on melanoma cells. It was demonstrated that β-carotene alone (1 µM) did not affect BRAF or ERK expression in melanoma cell lines carrying the B-RAF mutation (A2058 cell line), while in combination with B-RAFi (PLX), it enhanced the suppression of B-RAF activation and of the downstream Erk1/2 effector, induced by PLX [92], suggesting its potential use as an adjuvant for target-based therapy.…”
Section: Carrot Compounds and Their Role In Cell Survival Proliferati...mentioning
confidence: 99%
“…Anti-proliferative, anti-inflammatory, anti-apoptotic, anti-metastatic, ABC efflux transporter modulator [89][90][91][92]97] Antocianins Cytotoxic [93] 6-Methoximellein Anti-inflammatory, anti-metastatic [94] Falcarinol (FaOH)…”
Section: Compounds Biological Effects In Cancer Referencesmentioning
confidence: 99%